Phonetic Distance Tools Used in Linguistics - Uzun, Cemile (Mersin University, 2024)
Studies measuring the phonetic distance between languages are quantitative investigations aimed at exploring linguistic diversity. These studies reveal how specific words or linguistic structures vary across different regions. The goal of the study is to determine which tools are used to measure the phonetic distance of languages and to classify these tools according to the methods they employ. For this purpose, research on phonetic distance from the past to the present has been examined. In this respect, the study will guide research that aims to analyze phonetic distances between languages and develop phonetic distance measurement tools. Articles, books, and theses regarding phonetic distance concerning languages or dialects have been identified. The methodology sections of these identified studies have been analyzed and compared. Studies with the same data collection and analysis methods have been consolidated. It has been found that three types of methods are used to calculate and analyze the differences between languages and dialects: traditional, perceptual, and computational.

Diller arasındaki fonetik mesafeyi ölçen çalışmalar, dil çeşitliliğinin araştırılmasına yönelik niceliksel araştırmalardır. Bu çalışmalar, belirli kelimelerin veya dil yapılarının farklı bölgeler arasında nasıl değiştiğini ortaya koyar. Çalışmanın amacı, dillerin fonetik mesafesini ölçmek için hangi araçların kullanıldığını belirlemek ve bu araçları kullandıkları yöntemlere göre sınıflandırmaktır. Bu amaçla, geçmişten günümüze kadar fonetik mesafe ile ilgili çalışmalar incelenmiştir. Bu yönüyle çalışma, diller arasındaki fonetik mesafeyi analiz etmek, fonetik mesafe ölçüm araçları geliştirmek isteyen araştırmalara rehberlik edecektir. Diller veya lehçeler hakkında yapılmış fonetik mesafe ile ilgili makaleler, kitaplar ve tezler belirlenmiştir. Belirlenen çalışmaların yöntem bölümleri analiz edilmiştir ve karşılaştırılmıştır. Aynı veri toplama ve analiz etme yöntemine sahip çalışmalar birleştirilmiştir. Diller ve lehçeler arasındaki farklılıkları hesaplamak ve analiz etmek için geleneksel, algısal ve hesaplamalı yöntem olmak üzere üç çeşit yöntemin kullanıldığı görülmüştür.
Dilbilimde Kullanılan Ses Bilgisi Mesafe Araçları
Keywords: Linguistic Structures (Incl. Phonology; Morphology and Syntax); Dilsel Yapılar (Fonoloji; Morfoloji ve Sözdizimi dahil); Computational Linguistics; Hesaplamalı Dilbilim